Image of Women Character in Diddo Gaaru Short Story - Yuliani Rahmah; Nur Sawiji (IZUMI, 2022)
This research is conducted to grasp the image of women and gender inequality experienced by female characters in the Diddo Gaaru short story. The method used in this research is a literature study in which primary data obtained from the short story Diddo Gaaru are then analyzed using feminist literary criticism theory and presented descriptively. It is concluded that there are four forms of gender inequality in this short story: marginalization, subordination, stereotype, and violence as for the image of women in this short story, including ten images that, as a whole, describe the image of oppressed women. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor